Condensate losses and oscillations induced by Rydberg atoms. (10th February 2017) - Karpiuk, Tomasz; Brewczyk, Mirosław; Rzążewski, Kazimierz; Gaj, Anita; Krupp, Alexander T; Löw, Robert; Hofferberth, Sebastian; Pfau, Tilman
Abstract: We numerically analyze the impact of a single Rydberg electron onto a Bose–Einstein condensate. Both S - and D -Rydberg states are studied. The radial size of S - and D -states are comparable, hence the only difference is due to the angular dependence of the wavefunctions. We find the atom losses in the condensate after the excitation of a sequence of Rydberg atoms. Additionally, we investigate the mechanical effect in which the Rydberg atoms force the condensate to oscillate. Our numerical analysis is based on the classical fields approximation. Finally, we compare numerical results to experimental data.